2015
DOI: 10.3945/jn.114.207290
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Is Positively Associated with Calcium Absorption among Postmenopausal Thai Women with Low Calcium Intakes,

Abstract: These findings suggest that vitamin D status is an important determinant of calcium absorption among Thai women with low calcium intakes, and cassia may be a readily available source of calcium in this population. Furthermore, these data indicate that serum 25(OH)D concentrations may affect PTH elevation in postmenopausal women with low calcium intakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A possible mechanism for these observations could involve hepcidin inhibition of iron and intracellular ROS levels, which increases bone formation and decreases bone resorption and results in elevated bone mass. Compared with traditional osteoporosis therapies, such as calcium and vitamin D supplements, for inhibiting osteoclast activity or promoting osteoblast bone formation function, this novel iron reduction method seems suitable for postmenopausal osteoporosis , Song et al 2014, Sirichakwal et al 2015, Miller et al 2016. It has been reported that postmenopausal women often suffer from iron accumulation, and traditional treatment has often been ineffective for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism for these observations could involve hepcidin inhibition of iron and intracellular ROS levels, which increases bone formation and decreases bone resorption and results in elevated bone mass. Compared with traditional osteoporosis therapies, such as calcium and vitamin D supplements, for inhibiting osteoclast activity or promoting osteoblast bone formation function, this novel iron reduction method seems suitable for postmenopausal osteoporosis , Song et al 2014, Sirichakwal et al 2015, Miller et al 2016. It has been reported that postmenopausal women often suffer from iron accumulation, and traditional treatment has often been ineffective for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of phytate was also clear for wheat flour products, which showed higher calcium absorption than wheat bran products, which are rich in phytate [ 86 ]. Data reported in Table 5 show also that foods with low amounts of both phytate and oxalate, such as cassia leaves (42.6%), winged beans (39.1%) and the ivy gourd (47.6%) have a high calcium absorption [ 81 , 114 ]. Mineral water has been shown to be a source of absorbable calcium [ 110 , 118 ] but concentrations are relatively low, so this would need considerable amounts of consumption to make meaningful contributions to overall calcium intake.…”
Section: Calcium Absorption From Foodsmentioning
confidence: 99%
“…Estrogen deficiency is one of the most important factors contributing to osteopenia and it results in various intestinal environmental changes such as alteration of gut microbiota [ 13 ]. Although estrogenic hormonal imbalance may be affected by nutrient bioavailability [ 14 , 15 ], there is a dearth of studies on the effect of physical ovariectomy (OVX) and subsequent hormonal imbalance on the bioavailability of phytochemicals such as genistein remain. One hypothesis is that OVX-induced hormonal imbalance affects gut microbiota populations, thereby affecting the bioavailability of phytochemicals such as genistein.…”
Section: Introductionmentioning
confidence: 99%